2010
DOI: 10.3390/e12112268
|View full text |Cite
|
Sign up to set email alerts
|

Using Quantum Computers for Quantum Simulation

Abstract: Numerical simulation of quantum systems is crucial to further our understanding of natural phenomena. Many systems of key interest and importance, in areas such as superconducting materials and quantum chemistry, are thought to be described by models which we cannot solve with sufficient accuracy, neither analytically nor numerically with classical computers. Using a quantum computer to simulate such quantum systems has been viewed as a key application of quantum computation from the very beginning of the fiel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
106
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(108 citation statements)
references
References 137 publications
(179 reference statements)
1
106
0
1
Order By: Relevance
“…In general, DQS consists of three steps: initial state preparation |ψ(0) , unitary evolution U and the final measurement. These steps will be discussed in detail in the remainder of this subsections (see also (Brown et al, 2010)). …”
Section: A Digital Quantum Simulation (Dqs)mentioning
confidence: 99%
“…In general, DQS consists of three steps: initial state preparation |ψ(0) , unitary evolution U and the final measurement. These steps will be discussed in detail in the remainder of this subsections (see also (Brown et al, 2010)). …”
Section: A Digital Quantum Simulation (Dqs)mentioning
confidence: 99%
“…A recent review on using quantum computers for quantum simulations can be found in Ref. [11]. In addition, the theories of quantum complexity and entanglement are currently being established, a process which is still far from being complete.…”
Section: Introductionmentioning
confidence: 99%
“…However, as per [20] we can utilise basis transformations to further decompose the constituent semigroups {T (k) t }, and hence simplify the task of implementing channels from these semigroups, which is tackled in Section V. Firstly, note that for k = 1, L k simply generates Hamiltonian evolution, which can be simulated using a single unitary operation on a single qubit. We therefore focus on the generators of dissipative evolution, for which k ∈ [2,4]. We begin by defining unitary conjugation of a channel T t as the procedure transforming T t according to U † T t U, where U(ρ) = U ρU † for some unitary operator U .…”
Section: Decomposition Of Arbitrary Generatormentioning
confidence: 99%
“…However, equally as important is the development of methods for the simulation of open quantum systems [15,16], crucial for enhancing our understanding of nonequilibrium dynamics and thermalisation in a wide range of systems, from damped-driven spin-boson models to complex many fermion-boson models [2,3]. In particular, one would like to begin by simulating quantum channels, representing the most general quantum dynamics possible, and dynamical semigroups of quantum channels, which describe Markovian dynamics -continuous time processes resulting from interactions with a Markovian environment in the Born approximation [17].…”
Section: Introductionmentioning
confidence: 99%